Driving Sustainable Development Through MFCA and Green Accounting: The Role of Resource Efficiency - Sartika, Dewi; Helmina, Monica Rahardian Ary; Nor, Wahyudin (Economics and Business Solutions Journal, 2025)
This study aims to analyze the influence of Material Flow Cost Accounting (MFCA) and Green Accounting on Sustainable Development, with Resource Efficiency as a moderating variable. The independent variables in this study are Material Flow Cost Accounting and Green Accounting, while the dependent variable is Sustainable Development. Resource Efficiency serves as the moderating variable. The population in this study consists of employees working in consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX). The sample was selected using a simple random sampling technique, with a total of 84 respondents. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that Material Flow Cost Accounting and Green Accounting have a significant influence on Sustainable Development. Furthermore, Resource Efficiency strengthens the relationship between MFCA and Green Accounting with Sustainable Development
Keywords: Material Flow Cost Accounting; Green Accounting; Sustainable Development; Resource Efficiency